2001
DOI: 10.1038/sj.thj.6200084
|View full text |Cite
|
Sign up to set email alerts
|

p16/INK4a gene inactivation by hypermethylation is associated with aggressive variants of monoclonal gammopathies

Abstract: These findings suggest that the methylation of the p16 gene could be a relevant oncogenic event in the monoclonal gammopathies evolution being associated with the most aggressive forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Our reported prevalence of p16 methylation falls within the range of 10% to 51% reported in previous literature. 9,[17][18][19][20][21][22][23][24][25][26] The heterogeneity in methodology and sample sizes may explain such variation among studies. Although p16 methylation is slightly (but significantly) more prevalent in MM than SMM/MGUS and may be a marker of advance disease, our data did not confirm previous studies that suggested p16 methylation may contribute in the transformation from MGUS to MM as a substantial proportion of MGUS already harbors p16 methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Our reported prevalence of p16 methylation falls within the range of 10% to 51% reported in previous literature. 9,[17][18][19][20][21][22][23][24][25][26] The heterogeneity in methodology and sample sizes may explain such variation among studies. Although p16 methylation is slightly (but significantly) more prevalent in MM than SMM/MGUS and may be a marker of advance disease, our data did not confirm previous studies that suggested p16 methylation may contribute in the transformation from MGUS to MM as a substantial proportion of MGUS already harbors p16 methylation.…”
Section: Discussionmentioning
confidence: 99%
“…cells (37,38). It has been identified that there is an association between hypermethylation of SOCS-1 and the pathogenesis of different tumors, including chronic myeloid leukemia, human melanoma and gastric cancer (39)(40)(41) (43) failed to detect a correlation between P16 methylation and prognostic factors. P16 hypermethylation has been associated with progression of the disease, as the frequency of this phenomena increases as the disease progresses through its different stages of evolution, beginning at 0% at the preclinical phase or monoclonal gammopathy of undetermined significance, at 0% for the asymptomatic phase, and to 41.8% for symptomatic MM and 80% for plasma cell leukemia (3,4,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that the genetic predisposing factors involved in microsatellite polymorphism (7), single nucleotide polymorphism (SNP) (8,9), methylation (10), mutation as well as deletion (11). Various cytokines such as IL-6, TNF-α, IL-1β and immune regulatory molecules like CTLA-4 (cytotoxic T-lymphocyte antigen-4) as well as proto-oncogene such as p53, p16, nuclear factor IκB, etc., are reported to be the predisposing factors (11)(12)(13)(14)(15). In order to investigate the laboratory diagnostic characters of monoclonal gammopathies in large scale in China as well as to analyze the putative genetic predisposing factors, here in this study, we studied the immunological features of 2,007 cases of monoclonal gammopathies from 10,682 suspected samples for laboratory diagnostic confirmation or exclusion with serum protein electrophoresis (SPE), immunofixation electrophoresis (IFE), immunoglobulin (Ig) quantitation (rate nephelometry) as well as urine free light chain ELISA.…”
Section: Introductionmentioning
confidence: 99%